Komunikasi dan pemaknaan nilai kewirausahaan di hipmi bpc kota padang - Himni, Lailatul; Roem, Elva Ronaning; Miko, Alfan (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The phenomenon of entrepreneurship or what's knowing as entrepreneur this time involved a lot of young people. In the HIPMI organization, BPC Padang City also make young age a requirement to become member. Entrepreneur who have entrepreneurial values can survive in doing business development and they can also be said to win in competition. This achievement can't be separated from the role of communication. Communication experience played by entrepreneurs, verbal and non-verbal communication carried out by entrepreneur as leader can be effective communication so that it has an impact on business success. Through this qualitative research, the researcher will observe the experience of the role of entrepreneurial cultural communication. Researchers will find out how the role of cultural communication carried out by entrepreneurs can build and apply entrepreneurial values to their business. The value of entrepreneurship is the main key in achieving success. When someone has an entrepreneurial spirit, then of course they will continue to survive. The entrepreneurial value of entrepreneurs is very much needed in the business, because order to achieve their business goals and improve the quality of existing business competition. Keywords: Enterpreneur, Comunication Experiences, Meaning